Shape Shifting of Cup Shaped Particles on Growing poly (2-hydroxy ethyl methacrylate) Brushes by “Grafting From” Approach and Dissipative Particle Dynamics Simulation - Ifra; Singh A.; Saha S. (My University, 2025)
Controlled bending leading to shape shifted microparticles is indispensable for the targeted biomedical applications including advanced drug/cell delivery and has been one of the major research components in biomedical area for decades. Here, we report the shape-shifting of cup-shaped particles created by electrojetting from a blend of biodegradable polylactide (PLA) and biocompatible co-polymer (poly[methylmethacrylate-co-2-(2-bromopropionyloxy)ethyl methacrylate] (poly(MMA-co-BEMA))) containing ATRP (Atom Transfer Radical Polymerization) initiating moiety, at a ratio of 75:25. Surface initiated ATRP of HEMA (2-hydroxy ethyl methacrylate) was carried out for 1 hour to immobilize self-crosslinkable poly(HEMA) brushes onto the cup shaped particles which underwent controlled bending post polymer brush growth leading to the formation of spherical ball with one small opening (hole). However, no change of shape was observed while growing non-crosslinkable hydrophilic poly(DMAEMA) (poly(2-(Dimethylamino)ethyl methacrylate)) brush from the surface of cup shaped particles. To understand the underlying phenomena of shape shifting, simulation studies were also performed. Dissipative particle dynamics (DPD) simulation of the ATRP process at the cup surface further confirmed that the use of HEMA monomer indeed led to the desired compact modified structure of the cup particle due to the crosslinking connectivity across the interface. We have also calculated the radial distribution function (RDF) and radius of gyration to study the structure of modified particles. © 2020 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim